Excess Electron Transfer through DNA Duplexes Comprising a Metal‐Mediated Base Pair. Issue 43 (19th July 2017) - Hensel, Susanne; Eckey, Kevin; Scharf, Philipp; Megger, Nicole; Karst, Uwe; Müller, Jens
Abstract: Excess electron transfer through one set of DNA duplexes comprising either one or two metal‐mediated thymine–Hg II –thymine base pairs was studied. Towards this end, the metal‐mediated base pair(s) were introduced between an artificial nucleoside bearing a N, N, N′, N′ ‐tetramethyl‐1, 5‐diaminonaphthalene derivative (dN, acting as a photoinducible electron donor) and 5‐bromo‐2′‐deoxyuridine (dB, acting as an electron acceptor). Upon one‐electron reduction, dB loses a bromide ion. The amount of unreacted dB remaining after irradiation—determined by LC/ICP‐MS—was used to evaluate the charge‐transfer efficiency across the metal‐mediated base pair(s). Reference measurements with canonical adenine:thymine base pairs prove the applicability of this approach for the detection of charge transfer in DNA. The data indicate that, for the set of DNA duplexes under investigation, excess electron transfer across a thymine–Hg II –thymine base pair proceeds with low efficiency, comparable to the transfer across a thymine:thymine mispair. Two contiguous thymine–Hg II –thymine base pairs effectively shut down excess electron transfer. Abstract : A new method for an evaluation of the efficiency of excess electron transfer through DNA duplexes is introduced. Its application to the study of charge transfer across a thymine–Hg II –thymine base pair indicates a significant decline compared with a canonical base pair (see scheme).